(untitled) (Economic and Political Thought, 2010)
The aim of the article is to present the process of financial market integration within the European Union and its assessment. The article explains the concept of financial integration and presents steps taken by the European Union in order to integrate the financial market and the level of that integration, and also indicates challenges that the European Union must meet to further integrate its financial market. The analysis that was carried out lets the author state that the attempts to create a uniform financial market within the European Union have been unsuccessful so far. Nevertheless, the steps taken by the European Union, i.e. the implementation of FSAP, the introduction of the euro, common financial policy, TARGET or SEPA, greatly contributed to the increase of the level of the EU financial market integration. The development of the integration can be especially seen on the wholesale financial services market. Retail market keeps being poorly integrated. The 21st century financial crisis clearly showed that the process of integration requires an introduction of some changes which mainly regard the issues of financial market supervision.